International Adjudication as a Mode of EU External Governance? The WTO Seal Case*. (12th October 2016) - Krämer‐Hoppe, Rike U.; Krüger, Tilman
Abstract: The literature on EU external governance has greatly advanced our understanding of rule transfers beyond Europe's borders. Contributions highlight different modes of such EU external governance. This contribution proposes to add international adjudication as another form of EU external governance. Acknowledging the important role of judicial decision‐making in shaping the international order, this article uses the example of WTO adjudication to add to existing conceptualizations of EU external governance. In our view, WTO dispute settlement offers possibilities for the EU to transfer EU norms to the international level and beyond its own borders. As we illustrate through an exploratory case study of the recent WTO seal dispute, the EU's internal setup matters greatly for its success.